Cytokinin-Modulated Gene Expression in Excised Pumpkin Cotyledons - Chen, Chong-Maw (1985)
Comparison of two-dimensional polyacrylamide gel electrophoretic maps of proteins isolated from benzyladenine-treated and untreated pumpkin (Cucurbita pepo L. cv Halloween) cotyledons showed that the expression of certain proteins is enhanced, induced, or suppressed by the cytokinin treatment. The amount of poly(A)(+) mRNA isolated from cotyledons incubated with 10(−4) molar benzyladenine for five days was about four-fold over the water-incubated control. The activity of hydroxypyruvate reductase prepared from purified cotyledonous microbodies and analyzed by native gel electrophoresis is proportionally enhanced by sequentially higher concentrations (10(−9) to 10(−4) molar) of benzyladenine. Ethidium bromide (1 microgram per milliliter) did not inhibit hydroxypyruvate reductase activity; thus, the enzyme synthesis does not appear to be controlled by organelle genes. Hydroxypyruvate reductase synthesis is inhibited by cycloheximide, cordycepin, and to a certain degree by actinomycin D. These data support the view of a close association between cytokinin action and gene expression.